Pengaruh Pola Waktu Pemberian Pakan dengan Suplementasi Beberapa Level Vitamin C terhadap Performans Produksi dan Organ Fisiologis Ayam Broiler - Subekti, Kusnadidi (Fakultas Peternakan Universitas Jambi, 2009)
The purpose of this research is to evaluate effect of feeding time pattern that supplemented by several ascorbic acid level on production performance and physiological organs of broiler. Variables observed were average daily gain (ADG), feed consumption, feed convertion, relative growth rate, income over feed cost (IOFC), production index, weight of tyroid gland, liver, kidney and feather percentage. Two hundreds unsex broiler CP 707 COBB strain were used. These Chickens housed per cage ; dimensions were 1 x 1 x 0,6 m. Metabolizable energy and crude protein content in diet were 3000 ccal/kg and 20%. Water was suplied for ad libitum.Treatments were arranged as a Completely Randomized Designs in Factorial Designs. There are two factor ; factor A ; feeding time (W09 and W18) and factor B ; ascorbic acid levels (L0, L50, L100, L150 mg/l water), with fifth replication. Result of this experiment indicated there are zero interaction between feeding time and ascorbic acid levels, and feed consumption, weight of tyroid, liver, kidney, and feather percentage were no influenced (P > 0.05) by treatments. However, relative growth rate were affected (P < 0.05) and highly affected (P < 0.01) on average daily gain and feed convertion. 15 hours feeding time pattern with 100 mg/l ascorbic acid level gived the best response on income over feed cost (IOFC) and production indexs. In conclution, 14 hours feeding time pattern with 100 m/l ascorbic acid level gived the best result on average daily gain (ADG), feed convertion, relative growth rate, income over feed cost and production indexs.